2012
DOI: 10.15288/jsad.2012.73.865
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Disadvantage and Adult Alcohol Outcomes: Differential Risk by Race and Gender

Abstract: ABSTRACT. Objective:We examined whether relationships of neighborhood disadvantage with drinker status, heavy drinking, alcoholrelated consequences, and dependence differed by race and/or gender. We hypothesized that neighborhood disadvantage would be negatively associated with drinker status but positively associated with heavy and problem drinking, with more pronounced relationships among African American and Hispanic men than other groups. Method: Data consisted of nationally representative, randomly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 37 publications
6
90
2
2
Order By: Relevance
“…It is asserted that interaction with peer groups encourages experimentation with psychoactive substances among school-going adolescents (McLeod, 2016). Similarly, PASU has previously been related to school neighborhood factors (Karriker-Jaffe et al, 2012;Milam, Furr-Holden, Harrell, Whitaker, & Leaf, 2012;Oman, Tolma, Vesely, & Aspy, 2013). Such a state of affairs catalyzes indulgence in substance use among adolescents and their peers, as previously opined by the social learning theorists.…”
Section: Introductionmentioning
confidence: 70%
“…It is asserted that interaction with peer groups encourages experimentation with psychoactive substances among school-going adolescents (McLeod, 2016). Similarly, PASU has previously been related to school neighborhood factors (Karriker-Jaffe et al, 2012;Milam, Furr-Holden, Harrell, Whitaker, & Leaf, 2012;Oman, Tolma, Vesely, & Aspy, 2013). Such a state of affairs catalyzes indulgence in substance use among adolescents and their peers, as previously opined by the social learning theorists.…”
Section: Introductionmentioning
confidence: 70%
“…34 (More recent manuscripts have heeded this recommendation and have found qualitatively different effects for men and women, although the directions have been inconsistent). [35][36][37][38][39] In the review by Karriker-Jaffe, consistent associations between neighborhood disadvantage and heavy drinking were reported. 34 More recent studies not included in this review have corroborated this finding; although the frequency of alcohol use generally increases in higher SES neighborhoods, binge drinking, heavy alcohol use, and other risky drinking behaviors tend to decrease, 35,40 although the evidence is mixed.…”
Section: Introductionmentioning
confidence: 87%
“…[35][36][37][38][39] In the review by Karriker-Jaffe, consistent associations between neighborhood disadvantage and heavy drinking were reported. 34 More recent studies not included in this review have corroborated this finding; although the frequency of alcohol use generally increases in higher SES neighborhoods, binge drinking, heavy alcohol use, and other risky drinking behaviors tend to decrease, 35,40 although the evidence is mixed. [41][42][43] Similar relationships have been found for other neighborhood measures, such as neighborhood disorder, cohesion, unemployment, and deterioration of the built environment.…”
Section: Introductionmentioning
confidence: 87%
“…Most (73 %) were employed; slightly more than half (56 %) had incomes of $60,000/year or less, and 64 % had attended at least some college. For a more detailed description of the sample, see Karriker-Jaffe et al 60 Overall, 5.0 % of respondents reported experiencing two or more negative drinking consequences in the past year. Drinking consequences were common among respondents living in disadvantaged and African American neighborhoods and among respondents who reported more pro-drunkenness norms and higher consumption of high-alcohol-content beverages, especially spirits/liquor (Table 1).…”
Section: Descriptive Analysesmentioning
confidence: 99%
“…In contrast, other studies have found no support for the disadvantage hypothesis and substance use, 25 and still other studies have shown mixed results depending on the measure of neighborhood socioeconomic status 26 or the outcome examined. 27,28 Karriker and colleagues 29 found neighborhood disadvantage was associated with elevated risk of negative drinking consequences, particularly for White women and African American men but not to alcohol dependence symptoms. Although prior studies have examined neighborhood influences on drinking behavior, few studies have used large, nationally representative samples or examined different dimensions of neighborhood disadvantage or multiple outcomes.…”
Section: Introductionmentioning
confidence: 99%